2012
DOI: 10.4238/2012.october.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the pathogenic plant fungus Rhizoctonia solani (Ceratobasidiaceae) isolated from Egypt based on protein and PCR-RAPD profiles

Abstract: ABSTRACT. Twenty-one isolates of Rhizoctonia solani were categorized into three anastomosis groups consisting of AG-4-HG-I (eight isolates), AG-2-2 (nine isolates) and AG-5 (four isolates). Their pathogenic capacities were tested on cotton cultivar Giza 86. Pre-emergence damping-off varied in response to the different isolates; however, the differences were not significant. Soluble proteins of the fungal isolates were electrophoresed using SDS-PAGE and gel electrophoreses. A dendrogram of the protein banding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…Out of these, group Ia (Rsl-1, Rsl-43 and Rsl-44) isolates were collected from Zone-V and group IIa isolates (Rsh-3 and Rss-12) were collected from Zone-II. These results are in accordance with earlier studies conducted by Singh et al (2002), Guleria et al (2007, and Mahmoud et al (2012) where partial relationship was observed between level of virulence and geographic origin based on RAPD profiles.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Out of these, group Ia (Rsl-1, Rsl-43 and Rsl-44) isolates were collected from Zone-V and group IIa isolates (Rsh-3 and Rss-12) were collected from Zone-II. These results are in accordance with earlier studies conducted by Singh et al (2002), Guleria et al (2007, and Mahmoud et al (2012) where partial relationship was observed between level of virulence and geographic origin based on RAPD profiles.…”
Section: Discussionsupporting
confidence: 93%
“…(2007), and Mahmoud et al. (2012) where partial relationship was observed between level of virulence and geographic origin based on RAPD profiles.…”
Section: Discussionmentioning
confidence: 95%
“…Twenty-one isolates of Rhizoctonia solani were characterized by RAPD-PCR. There was a partial relationship between GS and anastomosis groups or level of virulence or geographic origin on the basis of the RAPD dendrogram (Mahmoud et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The sequences were compared with others deposited in databanks for species definition. Mahmoud et al, 2012Mahmoud et al, 2012Mahmoud et al, 2012Batista et al, 2008Batista et al, 2008Batista et al, 2008Batista et al, 2008Batista et al, 2008Batista et al, 2008 (GACA)4 (AGAG)4G (GTG)5 5´-GACAGACAGACAGACA 5´-AGAGAGAGAGAGAGAGG 5´-GTGGTGGTGGTGGTG Batista et al, 2008Batista et al, 2008Hatti et al, 2010 Figure 1. Phylogenetic analysis of the 5.8S-ITS and -tubulin gene sequences from the Aspergillus flavus isolates.…”
Section: Molecular Identification Of the Isolatesmentioning
confidence: 99%